Implementation of Islamic Economics: A Study of Pragmatic Thinking by Charles S. Peirce, Amin Abdullah, and Kim Knott - Melis; Abdullah, Amin (Department of Islamic Financial Management, Faculty of Economics and Islamic Business, Sunan Kalijaga State Islamic University, Yogyakarta, Indonesia., 2023)
Background: As Charles S. Pierce believed in his book